EXPLORING RELIGIOUS MODERATION IN THE HALAQAH EDUCATION SYSTEM OF ISLAMIC BOARDING SCHOOLS IN SOCIO-HISTORICAL PERSPECTIVE - Syahril, Syahril; Fajri, Suryadi; Duski, Fatmi Fauzani; Putri, Aulia Rahmi; Zulpadrianto, Zulpadrianto (Journal of Contemporary Islam and Muslim Societies, 2024)
This study explores religious moderation within the halaqah education system in West Sumatra, emphasizing the integration of tolerance, harmony, and local wisdom into its curriculum and teaching methods. Employing a descriptive qualitative approach, the research investigates how halaqah education shapes the character of santri and upholds moderate Islamic traditions in the community. The findings reveal that halaqah education remains highly relevant in West Sumatran society due to its ability to adapt to contemporary developments while preserving traditional values. This system has proven effective in fostering religious moderation, promoting tolerance, and nurturing respect for diversity. Consequently, halaqah education serves not only as a platform for transmitting religious knowledge but also as a tool for developing the character of santri to be moderate and open-minded. The study concludes that halaqah-based education significantly contributes to sustaining moderate Islamic traditions, addressing the challenges of modernity, and enhancing social cohesion in a multicultural context.Keywords: Halaqah, religious moderation, local wisdom, West Sumatra